การพัฒนากิจกรรมการเรียนรู้โดยใช้เทคนิค CIRC ร่วมกับผังกราฟิก เพื่อส่งเสริมความสามารถในการอ่านเพื่อความเข้าใจภาษาไทย สำหรับนักเรียนชั้นประถมศึกษาปีที่ 1 A DEVELOPMENT OF LEARNING ACTIVITIES BY USING THE CIRC TECHNIQUE WITH GRAPHIC ORGANIZERS ENHANCE THAI - วรรณบุตร, เบญจวรรณ; ปาณาวงษ์, ชำนาญ (วารสารวิจัยทางการศึกษา คณะศึกษาศาสตร์ มหาวิทยาลัยศรีนครินทรวิโรฒ, 2020)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) สร้างและหาดัชนีประสิทธิผลกิจกรรมการเรียนรู้โดยใช้เทคนิค CIRC ร่วมกับ ผังกราฟิก 2) ทดลองใช้กิจกรรมการเรียนรู้โดยใช้เทคนิค CIRC ร่วมกับผังกราฟิก 3) ศึกษาความพึงพอใจของนักเรียนที่มีต่อกิจกรรมการเรียนรู้โดยใช้เทคนิค CIRC ร่วมกับผังกราฟิก กลุ่มตัวอย่างที่ใช้ในการวิจัยเป็นนักเรียนชั้นประถมศึกษาปีที่ 1 โรงเรียนบ้านเขาดินไพรวัน จำนวนทั้งสิ้น 26 คน ได้มาจากการเลือกแบบเจาะจง เครื่องมือที่ใช้ในการวิจัยประกอบด้วย เครื่องมือที่ใช้ในการทดลองคือ แผนการจัดกิจกรรมการเรียนรู้ จำนวน 6 แผน และเครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูล ได้แก่ แบบวัดความสามารถในการอ่านเพื่อความเข้าใจ กลุ่มสาระการเรียนรู้ภาษาไทย และแบบสอบถามความพึงพอใจ การวิจัยครั้งนี้วิเคราะห์ข้อมูลโดยหาค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน ค่าดัชนีประสิทธิผล และใช้สถิติทดสอบทีแบบไม่อิสระ ต่อกัน ผลการวิจัยพบว่า 1) กิจกรรมการเรียนรู้โดยใช้เทคนิค CIRC ร่วมกับผังกราฟิก มี 4 ขั้นตอน ประกอบด้วย ขั้นตอนที่ 1 ขั้นนำเสนอบทเรียน ขั้นตอนที่ 2 ขั้นฝึกทำงานกลุ่ม ขั้นตอนที่ 3 ขั้นตอนการทดสอบ ขั้นตอนที่ 4 ขั้นตระหนักความสำเร็จของกลุ่ม มีความเหมาะสมอยู่ในระดับมากและมีค่าดัชนีประสิทธิผล 0.5185 2) นักเรียนมีความสามารถด้านการอ่านเพื่อความเข้าใจหลังเรียนสูงกว่าก่อนเรียนอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 3) ความพึงพอใจของนักเรียนต่อกิจกรรมการเรียนรู้โดยใช้เทคนิค CIRC ร่วมกับผังกราฟิกที่พัฒนาขึ้น อยู่ในระดับมากที่สุด คำสำคัญ : กิจกรรมการเรียนรู้, เทคนิค CIRC, ผังกราฟิก, การอ่านเพื่อความเข้าใจ ABSTRACT The purpose of this study were 1) To create and find effectiveness index of the learning activities by using the CIRC technique with graphic organizers. 2) To try out the learning activities by using the CIRC technique with graphic organizers. 3) To study the satisfaction of the learning activities by using the CIRC technique with graphic organizers. The samples were grade 1 students in Bankhowdinphraiwan school, consisting of 26 people, who were acquired by the specific selection method. The tools used in this research were tools used in the experiment 1. The learning activities by using the CIRC technique with the 4 steps graphic organizers 6 lesson plans. Tools used to collect data were 1) A Thai language reading comprehension measurement form 2) A form to measure satisfaction. The statistics used for data analysis were mean (), standard deviation (S.D.), effectiveness index (E.I.), statistical values t-test Dependent. The research findings revealed that 1) The learning activities by using the CIRC technique together with the 4 steps graphic organizers consisting of 1. presentation stage, 2. group work practice stage 3. testing stage and 4. Realize the group’s success stage were suitable at a high level and had an effective index of 0.5186. 2) The students had better reading comprehension ability after studying than before by using the learning activities by using the CIRC technique with graphic organizers with statistical significance at the level of .05 and 3) Students were satisfied with the learning activities by using the CIRC technique with graphic organizers enhance Thai reading comprehension ability in the highest level. Keywords: Learning Activities, CIRC Technique, Graphic Organizers, Reading Comprehension